2016
DOI: 10.5430/jct.v5n2p83
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Multimedia Learning: Influence of a Social Regulatory Support on Learning Performance and on Collaboration

Abstract: This paper analyzes the effects of a support aimed at favoring the social regulatory processes in a computer-supported collaborative learning (CSCL) environment, specifically in a comprehension task of a multimedia text about Psychology of Communication. This support, named RIDE (Saab, van Joolingen, & van Hout-Wolters, 2007;2012), consists in the instruction, prior to the learning task, from a series of communication rules extracted from literature about effective collaboration. The study was carried out with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Fukfon, Sriwichai, Chairinkhom, & Tanyapansin (2018) also found that relationship factors between professors and students has a negative correlation to stress, with a significance level of .01. Acuña & López-Aymes (2016) found that the condition with social regulatory support promoted higher quality concept maps; however, the social regulatory support had a significant effect on the levels of collaboration perceived by the team members. In the conclusions are pointed the reach of these results for the design and implementation of collaborative interventions, based on the use of multimedia materials.…”
Section: Discussionmentioning
confidence: 83%
“…Fukfon, Sriwichai, Chairinkhom, & Tanyapansin (2018) also found that relationship factors between professors and students has a negative correlation to stress, with a significance level of .01. Acuña & López-Aymes (2016) found that the condition with social regulatory support promoted higher quality concept maps; however, the social regulatory support had a significant effect on the levels of collaboration perceived by the team members. In the conclusions are pointed the reach of these results for the design and implementation of collaborative interventions, based on the use of multimedia materials.…”
Section: Discussionmentioning
confidence: 83%
“…Researchers (e.g. Acuña and L opez-Aymes, 2016;Clark and Mayer, 2016;de Sousa et al, 2017;Evans and Gibbons, 2007;Farias et al, 2007) provide evidence suggesting that students, both at university and lower levels, show significant differences when learning from multimedia content as opposed to traditional learning. Likewise, studies show that learners' success through multimedia learning environments would increase meaningfully.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers (e.g. Acuña and López-Aymes, 2016; Clark and Mayer, 2016; de Sousa et al. , 2017; Evans and Gibbons, 2007; Farias et al.…”
Section: Introductionmentioning
confidence: 99%